Fluorescence detection of ethylmorphine through terbium complex. Issue 7 (8th August 2020) - Boureima Mahamane, Issoufou; Kaftanoglu, Sezen Irem; Caglayan, Mehmet Gokhan
Abstract: In this paper, new fluorescence assay was developed for ethylmorphine based on complex formation with terbium. Ethylmorphine is an opiate and it is prone to be abused. Therefore, it is one of the frequently tested analytes in screening tests. The developed assay can be used as a screening test for opiate alkaloids since it produces fluorescence ON response with a simple experiment, and it may be used for an alternative/additional test to avoid false negative/positive results in regular screening tests. The assay can also be used for the quantitative analysis of ethylmorphine.